Investigación y gestión docente en la carrera de Ingeniería Agronómica extensión La Maná de la Universidad Técnica de Cotopaxi. Propuesta dotar de un sistema de capacitación en la investigación educativa. - Trávez Trávez, Rául Clemente (2014)
The research begins with a diagnosis revealed as a scientific problem, the shortcomings in the process of scientific formation of agronomic engineering professionals in the solution to the educative problems in an determined scholar context. The object of the research is the process of research training of the agronomic professional; the field is the management of training in agronomic research and objective: the design of a socio transforming management strategy for research training of agronomists, supported by a management model of agricultural research training. This research will help to improve the processes of transformation of educational problems from the application of a logic of agricultural research and its epistemological novelty lies in revealing an integrative logic between agronomic axiological orientation, management of educational practice and implementation of agricultural research as a core management training research. Research and teaching management in the Agricultural Engineering career of the Cotopaxi Technical University according to this work, it was observed that started working in this area how to guide research projects in academic management and to contribute to the process of teaching and learning.